A neurocognitive approach to studying processes underlying parents’ gender socialization - Portengen, Christel M.; van Baar, Anneloes L.; Endendijk, Joyce J. (Frontiers in Psychology, 2023)
Parental gender socialization refers to ways in which parents teach their children social expectations associated with gender. Relatively little is known about the mechanisms underlying gender socialization. An overview of cognitive and neural processes underlying parental gender socialization is provided. Regarding cognitive processes, evidence exists that parents’ implicit and explicit gender stereotypes, attitudes, and gendered attributions are implicated in gender socialization. Other cognitive factors, such as intergroup attitudes, gender essentialism, internal motivation for parenting without gender stereotypes, gender identity, and conflict resolution are theoretically relevant mechanisms underlying gender socialization, but need further investigation. Regarding neural processes, studies demonstrated that attentional processing, conflict monitoring, behavior regulation, and reward processing might underlie stereotypes and biased behavior. However, more research is necessary to test whether these neural processes are also related to parental gender socialization. Based on this overview, a framework is presented of neural and cognitive factors that were theoretically or empirically related to gender socialization.